2008
DOI: 10.1177/1088868308323223
|View full text |Cite
|
Sign up to set email alerts
|

The Political Solidarity Model of Social Change: Dynamics of Self-Categorization in Intergroup Power Relations

Abstract: Social and political change involves a challenge to the status quo in intergroup power relations. Traditionally, the social psychology of social change has focused on disadvantaged minority groups collectively challenging the decisions, actions, and policies of those in positions of established authority. In contrast, this article presents a political solidarity model of social change that explores the process by which members of the majority challenge the authority in solidarity with the minority. It is argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
441
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(472 citation statements)
references
References 115 publications
(177 reference statements)
10
441
0
6
Order By: Relevance
“…Arguably, this recognition and the willingness of majority members to join in collective action against discrimination is just as important for changing intergroup relations (Subašić, Reynolds, & Turner, 2008). However, more work is needed on majority group members' willingness to become actively involved in fighting discrimination (Banfield & Dovidio, 2013;Saguy, Dovidio, & Pratto, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, this recognition and the willingness of majority members to join in collective action against discrimination is just as important for changing intergroup relations (Subašić, Reynolds, & Turner, 2008). However, more work is needed on majority group members' willingness to become actively involved in fighting discrimination (Banfield & Dovidio, 2013;Saguy, Dovidio, & Pratto, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further, successful involvement of the FD personnel, at all levels, requires evidence based feed-back of their findings to be evaluated and put into practice (McCormack et al, 2002).The Swedish welfare sector changes constantly, and it is important to follow these changes and tailor new methods at the same pace (Bergmark, 2000). The Swedish welfare philosophy is that the power relations should be based on solidarity (Subasic, Reynolds, & Turner, 2008). On the other hand it was found that the social and care system has a tendency to be more mechanistic with regards to financial control as a result of the "top-down" organisation tradition.…”
Section: Discussionmentioning
confidence: 99%
“…Theories of collective action argue that third parties within the conflict context and outsiders beyond the conflict context may intervene through collective action (Simon & Klandermans, 2001;Subašić, Reynolds, & Turner, 2008, Thomas, McGarty, & Mavor, 2009), though there is much less empirical work for this position (for exceptions, see Saeri, Iyer, & Louis, 2015;Subašić, Schmitt, & Reynolds, 2011). The psychological pathway by which third parties and outsiders come to appraise a conflict and take collective action is also relatively unexplored (but see Saeri et al, 2015).…”
Section: Personal Values About Change and Status Quo Influence Outsidmentioning
confidence: 99%
“…Individuals who are psychologically (and geographically) external to group conflict may appraise the conflict quite differently from members of the belligerent groups. Work investigating these "outsiders" to conflict has typically conceptualised them as members of majority audiences who can influence the conflict by endorsing one of the two conflicting groups through a process of self-categorization, identification, and action on one group's behalf (Simon & Klandermans, 2001;Subašić et al, 2008). However, such an audience is already part of the intergroup context and thus has at least a minimal connection to, and understanding of, the groups involved in the conflict.…”
Section: Developments In Collective Action Researchmentioning
confidence: 99%